The Hybrid Actant of Integral Ecology and Sustainable Development. Why the Poor (and Women?) Must Be Protected Along With Rivers, Mountains, Birds and Forests... - Fontanille, Jacques; Lairesse, Julie (E|C, 2023)
The founding documents of the notions of environmental protection and sustainable development made it possible to broaden the theme of the environment to include socio eco nomic and cultural dimensions. The semiotic approach mainly questions the instances that participate in the two predicative configurations (to develop and to protect and in the construction of ecological actants, which are necessarily heterogeneous. This heterogeneity influences the roles that hybrid collective actants may play in the integrated configuration (develop+protect): between syncretic conceptions (everyone is a victim, a predator, and a protector at the same time) and discriminating concepti ons that oppose and distribute these roles between antagonistic collectives, the semiotic choices have major political implications. We focus on three international texts: Report of the United Nations Conference on the Environment (Stockholm 1972), Report of the Brundtland Commission on Environment and Development ( and Pope Francis encyclical Laudato Si' (2015)